Green Marketing Study Analysis in Comprehensive Business Strategy - Hendri Rudiawan; Tengku Kespandiar; Surya Bakti; Elizabeth Elizabeth; Halim Dwi Putra (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
A green marketing business strategy is a marketing approach that integrates environmental concerns into all aspects of a business, such as product, pricing, promotion, and distribution. It offers environmentally friendly products or services to build a positive brand image, consumer loyalty, and differentiation through the use of sustainable materials, low-pollution production processes, transparent promotions, recycling programs, and environmental partnerships. The purpose of this study is to analyze and examine green marketing in comprehensive business strategy. The research method in this study uses qualitative research and secondary data, such as books and journals, to answer the analysis of green marketing studies in comprehensive business strategies. The research results show that green marketing is a comprehensive business strategy that integrates environmental sustainability principles into the entire marketing process. To implement an effective green marketing strategy, companies can conduct an internal environmental analysis, clear goal setting, innovative product and process development, and transparent communication.